Analisis Faktor - Faktor Audit Eksternal Terhadap Reaksi Pasar - Djapri, Grace Karmel; Nindito , Marsellisa; Armeliza, Diah (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2025)
Market reaction represents how fundamental information of financial statements affects stock price and trading volume in the capital market. This research examines the effect of audit quality, audit opinion, audit report lag, and auditor switching towards market reaction. A quantitative method is applied in this research using secondary data collected from financial statements, stock price data, and composite stock price index (IHSG). Through purposive sampling technique, the research obtained 54 companies or 162-unit data from basic material companies listed on Bursa Efek Indonesia (BEI) during the period 2022 – 2024. The panel data regression analysis is used in this research using Eviews 13. The results indicate that audit quality and audit report lag have no significant effect on market reaction, whilst audit opinion and auditor switching significantly affect market reaction. These findings highlight the importance of fair and reliable financial reporting and auditor independence in reducing information risk and providing useful signals for investors.